CORRELATION BETWEEN SELF-EFFECTIVENESS IN BREASTFEEDING AND POST-BREAST DEPRESSION (CIPEEX, 2022)
GESTATION IS A PERIOD OF INTENSE CHANGES IN THE LIFE OF THE WOMAN AND HER FAMILY. AMONG THE PSYCHIATRIC DISORDERS OF PUERPERALITY, WE HIGHLIGHT POSTPARTUM DEPRESSION (PPD), WHICH IS CHARACTERIZED BY THE OCCURRENCE OF A MAJOR DEPRESSIVE EPISODE IN THE POSTPARTUM PERIOD. THIS DISORDER MAY INTERFERE WITH BREASTFEEDING, SINCE DEPRESSED MOTHERS ARE LESS LIKELY TO INITIATE OR MAINTAIN BREASTFEEDING, IN ADDITION TO CORRELATING WITH SELF-EFFICACY, THAT IS, THE MOTHER'S CONFIDENCE IN BREASTFEEDING. THE OBJECTIVE OF THIS STUDY IS TO CORRELATE POSTPARTUM DEPRESSION AND SELF-EFFICACY IN BREASTFEEDING AMONG WOMEN ATTENDING THE MILK BANK OF THE CITY OF ANÁPOLIS, GOIS, THROUGH THE APPLICATION OF TWO SCALES: THE SELF-EFFICACY SCALE IN BREASTFEEDING - REDUCED VERSION AND THE SCALE OF POSTPARTUM DEPRESSION IN EDINBURGH. IT IS A QUANTITATIVE CROSS-SECTIONAL STUDY. DATA COLLECTION WILL BE DONE BY SIGNING THE TERM OF FREE AND INFORMED CONSENT AND WILL BE ASSISTED BY AT LEAST ONE EMPLOYEE, WHO WILL BE TRAINED TO APPLY THE SCALES. THE RESULTS OBTAINED WILL BE ARCHIVED IN A DATABASE AND THE QUANTITATIVE ANALYZES WILL BE CARRIED OUT WITH DESCRIPTIVE STATISTICS BY THE SOFTWARE STATISTICAL PACKAGE FOR SOCIAL SCIENCE, USING PEARSON'S CORRELATION COEFFICIENT. THE PROVISION OF RESULTS TO THE RESEARCH INSTITUTION IS EXPECTED TO ASSIST IN MEASURES TO REDUCE THE RATE OF POSTPARTUM DEPRESSION AND, AT THE SAME TIME, INCREASE THE PROMOTION OF BREASTFEEDING.
Keywords: Breastfeeding. Self-efficacy. Baby blues.